P63 expression in pleomorphic adenoma and Mucoepidermoid carcinoma - Dr.C.MYTHILY; Dr.A.VASAHAR (International Journal of Pharma and Bio Sciences, 2016)
Tumors of salivary gland have diverse histological forms and unpredictable clinical behavior. The main application of immunochemistry in salivary gland tumors is to demonstrate the existence of myoepithelial/basal cells or luminal cells. Our objective is to evaluate the myoepithelial marker p63 in pleomorphic adenoma and mucoepidermoid carcinoma. The total number of specimens were 92, of which 41,were neoplastic. Pleomorphic adenoma was the commonest benign tumor accounting for 73.17%, Mucoepidermoid carcinoma was the most common malignant tumor accounting for 52.18%.In this study expression of p63 in pleomorphic adenoma have confirmed the role of myoepithelial cells in the histogenesis of this tumor and lack or minimal expression of p63 in mucoepidermoid indicates minimal myoepithelial cell differentiation in this tumors. IHC enhance the accuracy and be a helpful tool when the diagnosis cannot be assessed by histological examination such as cell of origin, cell proliferation and tumor protein expression.